Simple is as simple does: Plantinga and Ghazālī on divine simplicity. (October 2022) - McGinnis, Jon
Abstract: This study considers the notion of divine simplicity, the idea that God is not a composite of more basic features, and the criticisms by al-Ghazālī (d. 1111) and Alvin Plantinga of that doctrine. What is shown is that most of the argumentation against divine simplicity frequently credited to Plantinga had been nearly perfectly anticipated by al-Ghazālī. Moreover, in responding to a stronger form of divine simplicity, which Avicenna (d. 1037) had presented, than the Thomistic version that Plantinga attacks, Ghazālī develops 'new' arguments and moves that are still valuable and informative to the discussion of divine simplicity today.